2010
DOI: 10.1051/0004-6361/201014917
|View full text |Cite
|
Sign up to set email alerts
|

Orbital parameters of supergiant fast X-ray transients

Abstract: Context. Supergiant fast X-ray transient (SFXT) is a new class of the high-mass X-ray binary that shows short X-ray flares. The physical mechanism of SFXT short flares is still open for discussion. The accretion process of dense clumps in stellar wind onto neutron star (NS) has been proposed as the origin of such short flares. Aims. In order to examine the applicability of the clumpy wind scenario, we focus on the accretion mode that depends on orbital parameters. Our goal is to impose restrictions on the orbi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…On the other hand, accretion from a spherical wind, even if clumpy, seems unable to reproduce the characteristics of the Xray outbursts, such as the very short duration and strong peak (Romano et al 2009;Karino 2010). An abrupt transition between a region where high accretion rates can be achieved and the rest of the orbit, where accretion is suppressed, would be required.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, accretion from a spherical wind, even if clumpy, seems unable to reproduce the characteristics of the Xray outbursts, such as the very short duration and strong peak (Romano et al 2009;Karino 2010). An abrupt transition between a region where high accretion rates can be achieved and the rest of the orbit, where accretion is suppressed, would be required.…”
Section: Discussionmentioning
confidence: 99%
“…4) seems to agree with the scenario of a compact star accreting matter from the clumpy wind of the supergiant. Karino (2010) proposes different scenarios for this phenomenon, relating P and e. HD 74194 falls into the SFXT regime, but very near to the unstable orbit region, where stars could evolve towards coalescence.…”
Section: Discussionmentioning
confidence: 99%
“…Since SFXTs and faint HMXBs are newly recognized objects, complete parameter sets have not been provided. Additionally, since SFXTs have large eccentricities (Karino 2010), one dimensional approach may be restricted. However, it has been shown that some SG stars hosting SFXTs provide very large wind velocity.…”
Section: Discussionmentioning
confidence: 99%